2014
DOI: 10.1097/pcc.0000000000000044
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia-Sedation in PICU and Neurological Outcome

Abstract: The use of opioids during PICU admission was significantly associated with long-term adverse neuropsychological outcome independent of severity of illness scores in meningococcal septic shock survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
0
24
0
1
Order By: Relevance
“…42,43 While RESTORE focused on the process of how sedatives are administered, future studies should compare the best sedative agent for varied lengths of critical illness. Outcomes of interest include efficacy as well as an evaluation of the immediate risk-benefit ratio and an evaluation of the long-term impact of sedatives on neurocognitive development 44,45 and post-traumatic stress. 46 …”
Section: Discussionmentioning
confidence: 99%
“…42,43 While RESTORE focused on the process of how sedatives are administered, future studies should compare the best sedative agent for varied lengths of critical illness. Outcomes of interest include efficacy as well as an evaluation of the immediate risk-benefit ratio and an evaluation of the long-term impact of sedatives on neurocognitive development 44,45 and post-traumatic stress. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Mobility guidelines in adults typically employ sedation interruption, but this strategy may not translate directly to children 39 . In addition, evidence to support the optimal use of pain and sedation medications to minimize impact on delirium and neurodevelopmental disability are needed elements to support PICU rehabilitation therapies 4042 . To address these barriers and ultimately change ICU culture, centers have implemented multidisciplinary care pathways that include best practices with room for individualized care, coordination of care to optimize session scheduling between the bedside nurse and therapist, and curricula to educate healthcare and family providers on the potential benefits and safety measures of ICU rehabilitation 4345 .…”
Section: Discussionmentioning
confidence: 99%
“…Cohorts developed in Europe suggest that cognition, adaptive behavior, and verbal and visual memory in children who survive critical illness are within normal range, but tend to be significantly lower compared to healthy controls (22,70). Multiple contributing factors have been studied or are currently under study, including glucose control, sedation strategies, overall PICU LOS, and pre-PICU co-morbidities (22,70,72). …”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%
“…Hospital mortality was 25% and 17% of survivors had acquired moderate disability at hospital discharge, defined as discharge POPC ≥3 and increased ≥1 from baseline POPC (74). Recent studies of long-term outcomes of children with severe sepsis showed that, at 3–9 months post-discharge, children with sepsis-associated encephalopathy had significantly decreased global and verbal intelligence quotient, compared to control sepsis patients not admitted to the PICU and to healthy controls (7072). Evaluation of academic performance also revealed that children with sepsis who required PICU care had significantly higher rates of difficulties in completing school work, deterioration in academic performance, dividing attention and considering a variety of possible outcomes (70).…”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%